The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.jpcs.2010.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Spray drying: An alternative synthesis method for polycationic oxide compounds

Abstract: Synthesis of polycationic compounds by the spray-drying technique is an interesting alternative in the domain of aqueous precursor synthesis methods. Spray drying yields high quality samples with good reproducibility. The possibility of scaling up for production of large quantities with fast processing time is well established by the commercial availability of powders of various compositions. In this paper, we have discussed the advantages and limitations of this method and demonstrated its interest by synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This is a characteristic advantage of the spray drying technique, because other microencapsulation methods such as emulsification with solvent evaporation or inotropic gelation, specifically in the case of chitosan, demonstrates low drug loading efficiency when a high drug/chitosan is used. In addition, high chitosan concentrations can complicate the formation of spherical particles, mainly by the high viscosity of the drying solution [18]. Thus, the used parameters in spray drying and used drug/polymer ratio in this work lead to spherical particles with a high drug loading efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a characteristic advantage of the spray drying technique, because other microencapsulation methods such as emulsification with solvent evaporation or inotropic gelation, specifically in the case of chitosan, demonstrates low drug loading efficiency when a high drug/chitosan is used. In addition, high chitosan concentrations can complicate the formation of spherical particles, mainly by the high viscosity of the drying solution [18]. Thus, the used parameters in spray drying and used drug/polymer ratio in this work lead to spherical particles with a high drug loading efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the used parameters in spray drying and used drug/polymer ratio in this work lead to spherical particles with a high drug loading efficiency. Actually, what really contributes to increment viscosity of spray dried solution is the solute concentration and not drug/polymer ratio [5,18]. All samples were prepared with a fixed solute concentration of 0.5% w/v, in order to avoid a considerable viscosity increment of drying solution and to guarantee total dissolution of MTX and CH in the same organic solvent.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, magnetite can be easily formed starting from a mixture of Fe 2+ and Fe 3+ chlorides. Rivas-Murias et al [37] have reported the preparation of multimetallic (Bi, Ca, and Co; La, alkaline-earths, and Co or Mn) oxides: Stock solutions of the metal cations in acetic acid were prepared and spray dried using a cocurrent (the sprayed solution and hot airflow in the same direction) atomizer at 145-150°C. The powders were heated at 600°C for 2 h in air and calcined at higher temperatures.…”
Section: Spray Drying (Sd) and Related Methodsmentioning
confidence: 99%
“…The spray drying (SD) process has been a cornerstone in industrial manufacturing for a myriad of sectors for many years [181][182][183][184]. This technique involves the atomization of a liquid or slurry into a hot gas to rapidly produce dispersed powder particles, as depicted in Figure 6.…”
Section: Spray-drying (Sd)mentioning
confidence: 99%